TRICHOMONIASIS AMONG PREGNANT WOMEN IN DENPASAR CITY, BALI, INDONESIA - Luh Seri Ani; IGA Sri Darmayani (Journal of Global Pharma Technology, 2017)
Objective: This study aimed to investigate the incidence of T. vaginalis infection among pregnant women in the city of Denpasar, Bali, Indonesia and the associated factors. Methods: There were 376 pregnant women who participated in this study. Study participants were selected using cluster sampling method. These pregnant women were then interviewed and tested for T. Vaginalis infection (microscopic and culture). Results: Infection of T. vaginalis was found in 7.4% of the pregnant women. The infection is most likely to be found in pregnant women who have a lower education level, middle-class status and a history of STIs. It is also most likely if they never had any vaginal douching before if they have intercourse ≥3 times per week, use sitting toilets and use river water as their main water source. Type of toilet used, the practice of vaginal douching, and condom usage show a significant association with trichomoniasis among pregnant women (p values were 0.001, 0.002 and 0.000 respectively). Conclusion: Early detection of sexually transmitted infections (STIs), especially T. vaginalis infection, should be performed during prenatal care to avoid the negative effects on pregnancy.Keywords - pregnancy, STI, vaginal trichomoniasis